Dynamic calibration and seismic validation of numerical models of URM buildings through permanent monitoring data. (18th June 2021) - Cattari, Serena; Degli Abbati, Stefania; Alfano, Sara; Brunelli, Andrea; Lorenzoni, Filippo; da Porto, Francesca
Abstract: The construction of reliable numerical models is a key aspect within the seismic assessment of existing unreinforced masonry buildings. However, it is also a complex process due to the many uncertainties involved that can affect the structural response. In situ tests allow for the acquisition of data at a local scale. Nonetheless, supplementary information representing the global response is necessary to overcome other uncertainties (i.e., wall‐to‐wall connections or floor stiffness). To this end, data from ambient vibration tests (AVT) are useful to support seismic assessments. In fact, they allow for the identification of dynamic structural properties, which are useful in refining the calibration of numerical models. In addition, they address solutions for the aforementioned uncertainties. In this context, the paper presents how to efficiently exploit AVT data by using the case study of the former Courthouse of Fabriano (Ancona, Marche). This structure has been monitored since 2010 by the Italian Department of Civil Protection with a network of 28 seismic accelerometers. As a result, the equivalent frame (EF) model was calibrated in the linear field thanks to the dynamic identification provided under operational conditions. Subsequently, nonlinear dynamic analyses were performed using the recordings acquired during the Central Italy earthquake in 2016/2017. Even if the building experienced only a slight nonlinear behaviour, this comparison between the simulated and actual seismic response made it possible to validate the EF model, especially with reference to the capability in reproducing the amplification phenomena, which is extremely important for the assessment of structural and non‐structural components.